Substantia Nigra Stimulation Influences Monkey Superior Colliculus Neuronal Activity Bilaterally - Liu, Ping (American Physiological Society, 2008)
The inhibitory drive arising from the basal ganglia is thought to prevent the occurrence of orienting movements of the eyes, head, and body in monkeys and other mammals. The direct projection from the substantia nigra pars reticulata (SNr) to the superior colliculus (SC) mediates the inhibition. Since the original experiments in the SNr of monkeys the buildup or prelude neuron has been a focus of SC research. However, whether the SNr influences buildup neurons in SC is unknown. Furthermore, a contralateral SNr–SC pathway is evident in many species but remains unexplored in the alert monkey. Here we introduced electrical stimulation of one or both SNr nuclei while recording from SC buildup neurons. Stimulation of the SNr reduced the discharge rate of SC buildup neurons bilaterally. This result is consistent with activation of an inhibitory drive from SNr to SC. The time course of the influence of ipsilateral SNr on the activity of most SC neurons was longer (∼73 ms) than the influence of the contralateral SNr (∼34 ms). We also found that the variability of saccade onset time and saccade direction was altered with electrical stimulation of the SNr. Taken together our results show that electrical stimulation activates the inhibitory output of the SNr that in turn, reduces the activity of SC buildup neurons in both hemispheres. However, rather than acting as a gate for saccade initiation, the results suggest that the influence of SNr inhibition on visually guided saccades is more subtle, shaping the balance of excitation and inhibition across the SC.